2008
DOI: 10.1007/s11199-008-9453-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Extracurricular Science Intervention on Science Performance, Self-Worth, Social Skills, and Sexist Attitudes of Taiwanese Adolescents from Single-Parent Families

Abstract: A one group pretest-posttest design was used to investigate effects of an extracurricular science intervention on female and male junior high school students' science performance, self-worth, social skills, and sexist attitudes. Twenty-eight 8th grade Taiwanese students (16 boys, 12 girls) from single parent families participated in this study. Student responses to a questionnaire measuring their selfworth, social skills, and sexist attitudes, and interviews and classroom observations used for triangulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Gender stereotyping is prevalent in Taiwan, where culture and society have been influenced by centuries of male domination in which women were placed in a subordinate role and subject to unequal treatment. Hong, McCarthy Veach, and Lawrenz (2003) and Hong et al (2008) found that Taiwanese junior and senior high school boys were significantly more likely than girls to think in gender stereotypic ways. Although Taiwanese girls are educated to be diligent learners, they have significantly lower scores compared to boys in terms of their perception of science, self-concept in science, enjoyment of science, instrumental motivation to learn science, future-oriented motivation to learn science, and general interests in learning science and science related activities (OECD, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gender stereotyping is prevalent in Taiwan, where culture and society have been influenced by centuries of male domination in which women were placed in a subordinate role and subject to unequal treatment. Hong, McCarthy Veach, and Lawrenz (2003) and Hong et al (2008) found that Taiwanese junior and senior high school boys were significantly more likely than girls to think in gender stereotypic ways. Although Taiwanese girls are educated to be diligent learners, they have significantly lower scores compared to boys in terms of their perception of science, self-concept in science, enjoyment of science, instrumental motivation to learn science, future-oriented motivation to learn science, and general interests in learning science and science related activities (OECD, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from this study that girls are less involved in learning science during junior school and high schools. Hong et al (2003Hong et al ( , 2008 and Hong (2010) suggested a possible course of action-improve motivation of girls through encouragement to participate in extracurricular science activities. This has not been emphasized in the past.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, this section will focus on the few studies that have targeted math/science or healthcare interventions. Hong, Lin, and Veach (2008) implemented a science career intervention with 8 th grade students from single-parent households in Taiwan. The goal of the study was to both assess gender differences in self-worth, social skills, sexist attitudes, and learning in science and the post intervention impact on these aspects and science performance.…”
Section: Healthcare and Science/math Career Interventionsmentioning
confidence: 99%